Methyltransferase K-D-K-E motif influences the intercellular transmission of Newcastle disease virus - Xiao Li; Ye Zhao; Qing-Yuan Teng; Xue-Hui Zhang; Jia Xue; Guo-Zhong Zhang (Virulence, 2023)
We previously demonstrated that two methyltransferase motifs, K-D-K-E and G-G-D, affect the pathogenicity of Newcastle disease virus (NDV) by regulating mRNA translation and virus transmission. Here, we compared the infectious centre area produced by the NDV strain, rSG10, and methyltransferase motifs mutant rSG10 strains in DF-1 cells. The results show that intercellular transmission was attenuated by methyltransferase motif mutations. We further determined the ability of mutant viruses to spread in cell-free and cell-to-cell situations. Cell-free transmission of rSG10-K1756A was not reduced, indicating that cell-to-cell transmission of rSG10-K1756A was decreased. Using a donor and target system, we demonstrated that NDV can spread from cell-to-cell directly. Furthermore, by comparing the protein distribution area of three strains when treated with 2% agar overlay, we found that rSG10-K1756A was defective in cell-to-cell transmission. Tunnelling nanotubes (TNTs) are an important mode for cell-to-cell transmission. Treatment of cells with cytochalasin D (CytoD) or nocodazole to inhibit the formation of TNTs, reduced protein levels in all strains, but rSG10-K1756A was the least affected. These results indicate that mutation of the K-D-K-E motif is likely to restricted the spread of NDV via TNTs. Finally, we observed that matrix protein (M) and fusion protein (F) promoted the formation of cellular extensions, which may be involved in the cell-to-cell spread of NDV. Our research reveals a novel mechanism by which methyltransferase motifs affect the cell-to-cell spread of NDV and provides insight into dissemination of paramyxoviruses.